2017
DOI: 10.1007/s00204-017-2063-1
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of zebrafish larvae to evaluate drug-induced functional and morphological renal tubular alterations

Abstract: Prediction and management of drug-induced renal injury (DIRI) rely on the knowledge of the mechanisms of drug insult and on the availability of appropriate animal models to explore it. Zebrafish (Danio rerio) offers unique advantages for assessing DIRI because the larval pronephric kidney has a high homology with its human counterpart and it is fully mature at 3.5 days post-fertilization. Herein, we aimed to evaluate the usefulness of zebrafish larvae as a model of renal tubular toxicity through a comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 49 publications
(65 reference statements)
1
26
0
Order By: Relevance
“…This has already been shown e.g. for gentamicin, a member of aminoglycoside antibiotics, that demands very high concentrations when applied via fish water exposure in contrast to microinjection (Gorgulho et al, 2018, Hentschel et al, 2005, Westhoff et al, 2013. Additionally, while there are substantial structural and physiological similarities between nephrons of the zebrafish pronephros and the mammalian metanephros, the timing of nephron differentiation and kidney development as well as associated spatio-temporal geneexpression patterns differ between the zebrafish and other vertebrates (Gerlach and Wingert, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…This has already been shown e.g. for gentamicin, a member of aminoglycoside antibiotics, that demands very high concentrations when applied via fish water exposure in contrast to microinjection (Gorgulho et al, 2018, Hentschel et al, 2005, Westhoff et al, 2013. Additionally, while there are substantial structural and physiological similarities between nephrons of the zebrafish pronephros and the mammalian metanephros, the timing of nephron differentiation and kidney development as well as associated spatio-temporal geneexpression patterns differ between the zebrafish and other vertebrates (Gerlach and Wingert, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…We used the zebrafish line Tg(wt1b:GFP, cdh17:GFP); mitfa -/- ; roy -/+ or +/+ because it was the one that was previously used to define the lethality curves and characterize the renal tubular effects of gentamicin, paracetamol, and tenofovir ( Gorgulho et al, 2018 ). Drug susceptibility might change among different zebrafish lines.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed analysis on the functional and morphological renal alterations induced by gentamicin, paracetamol and tenofovir in zebrafish larvae showed tubular alterations similar to those described in man. In addition, electron microscopy revealed that tubular mitochondria were affected by the tested drugs, which points to severe metabolic alterations ( Gorgulho et al, 2018 ). This evidence led us to hypothesize that zebrafish larvae are an attractive model for toxicometabolomics studies.…”
Section: Introductionmentioning
confidence: 99%
“…Another polysaccharide that can be used for the evaluation of glomerular function in the zebrafish is inulin ( Figure 3 B). Inulin clearance measured after the intravascular injection of FITC-inulin is a good alternative to dextran in determining the glomerular filtration rate, especially because inulin is freely passing through the glomerular barrier and not reabsorbed or secreted from the proximal tubules, making it an ideal molecule to assess the glomerular filtration rate [ 63 , 64 ]. Inulin clearance is the current gold standard to assess the glomerular filtration rate (GFR) in humans [ 65 ]; however for this purpose, it has to be measured in the plasma and urine of patients.…”
Section: Assessment Of the Renal Phenotypementioning
confidence: 99%
“…When fused to GFP, VDBP has a molecular weight and electric charge approximate to that for human albumin (79.6 kDa vs. 66.5 kDa, and an isoelectric point 5.97 vs. 5.67, for VDBP-GFP vs. human albumin, respectively), so they should behave in a similar way at the glomerular filtration barrier [ 68 ]. In a transgenic zebrafish line expressing VDBP-GFP, the integrity of the glomerular barrier can be evaluated in a very similar way to that for high molecular weight fluorescent dextran by assessing fluorescence in the retinal vascular bed ( Figure 3 C), the cardinal vein or over the heart, or in the case of a defective glomerular barrier, in the proximal tubules [ 64 ]. Recently, 4D in vivo imaging using two-photon microscopy allowed for the simultaneous assessment of fluorescence intensity of the VDBP-GFP fusion protein in the vasculature and proximal tubules of live zebrafish larvae, which gives the opportunity for dynamic monitoring of the glomerular filtration barrier [ 71 ].…”
Section: Assessment Of the Renal Phenotypementioning
confidence: 99%